Analisis Pengembangan E-Learning Platform Pembayaran Pemerintah untuk Meningkatkan Kualitas Proses Pembayaran Tagihan Belanja Negara - Hasan Ashari; RN. Afsdy Saksono; Achmad Rinaldi Hidayat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The utilization of the Government Payment Platform (PPP) is a platform for work‑unit financial officers to ensure the accuracy and timeliness of state expenditure payments. This study analyzes the implementation of e‑learning of PPP on the Kemenkeu Learning Center (KLC) within the Budget and Treasury Education and Training Center an agile learning model grounded in the Learning Experience Platform (LXP) approach. The research employs a qualitative case study method with twelve (12) purposively selected informants representing policy, technical, pedagogical, and end‑user roles. Data were collected through in‑depth interviews and document analysis, and examined interactively across stages of data collection, condensation, presentation, and conclusion drawing, supplemented by method and source triangulation.Findings indicate key constraints: non‑specific participant segmentation by role, absence of dedicated learning time, limited interoperability between KLC and external platforms, insufficient per‑module discussion forums, and suboptimal use of AI (chatbots and recommendations). The study’s novelty lies in an agile LXP‑based model comprising: role‑scaled interactive curricula; a learning journey to personalize PPP competency pathways; AI‑driven chatbots serving as digital tutors and content recommendation engines; and cross‑platform collaboration compliant with information security standards. The conclusion underscores that agile PPP e‑learning has the potential to enhance learning effectiveness, efficiency, and relevance, while strengthening the competencies of financial managers within a continually transforming government payment ecosystem.